Organisation and management of water supplies in tropical Africa - Sandford, S. (International Livestock Centre for Africa, 1983)
Defines the major agricultural production zones of tropical Africa, with particular reference to the importance of land, livestock & water in each zone, & discusses traditional & modern strategies used to overcome water shortages, identifying factors which determine their adoption. Outlines the technical, administrative & environmental problems experienced in programmes for the development of water supplies in the past, examining the relationship between technology, equity, management & control. Considers the implications of past experience for planning water development in the future & includes proposals for future research which could lead to the formulation of better policies & development programmes.